Visualization of natural convection heat transport using heatline method in porous non-isothermally heated triangular cavity - Varol, Yasin; Öztop, Hakan Fehmi; Mobedi, Moghtada; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2008)
Natural convection heat transfer in a porous media filled and non-isothermally heated from the bottom wall of triangular enclosure is analyzed using finite difference technique. Darcy law was used to write equations of porous media. Dimensionless heatfunction was used to visualize the heat transport due to buoyancy forces. Three different boundary conditions were applied for the vertical and inclined boundaries of triangular enclosures as Case 1: both vertical and inclined walls were isothermal, Case 11; vertical wall was adiabatic and inclined one was isothermal, Case III; vertical wall is isothermal and inclined one is adiabatic. A cosine function was utilized to get non-isothermal wall condition. The study was performed for different aspect ratios (0.25 <= AR <= 1.0) and Darcy-modified Rayleigh numbers (100 <= Ra <= 1000). It was observed that heat transfer enhancement was formed when vertical and inclined walls were isothermal while bottom wall was at non-uniform temperature. Heat transfer from bottom wall did not vary when the value of aspect ratio was higher than 0.50. In addition, heatline visualization technique was a useful technique for non-isothermally heated and porous media filled triangular enclosures. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Porous medium; Natural convection; Triangular enclosure; Non-isothermal temperature profile; Heatline